METHODS OF TEACHING ENGLISH TO BLIND STUDENTS - Xidoyatxon Salimova Sodiqjon qizi (Лучшие интеллектуальные исследования, 2024)
The significance of learning foreign languages is widely recognized on a global scale. However, an unresolved challenge lies in effectively teaching foreign languages to individuals with disabilities, partic ularly those with visual impairments. This article aims to explore both the theoretical and practical aspects of teaching methods that can be employed in the classroom to enhance the language skills of foreign language learners with visual impairments. A visually impaired student can benefit greatly from the implementation of new and innovative methods to assist in their education. By providing practical help, such as specialized equipment and materials, educators can ensure that the student has the necessary tools to succeed in their studies.